Peran Customer Satisfaction Dalam Memediasi Strategi Pemasaran Online Dan Pengalaman Belanja Terhadap Repurchase Desicion - Mufidah, Rofiatul Adwiyah; Novie, Muhafidhah (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This researchaims todetermine the role’ of customer’ satisfaction in to mediating online’marketing strategies’’and’’shopping experiences’’on repurchase desires Type of quantitative research with a descriptive approach. The research sample was 72 respondents. Data collection techniques use questionnaires. The data analysis technique uses path analysis. Theresearch results show 1) online marketing strategies have a positive and;;significant influence oncustomer ‘satisfaction. 2) Online Marketing Strategy hasa positive and significant influence on Repurchase decisions. 3) Shopping experience has a’’positive and significant effect on customer satisfaction. 4) Shopping experience has a positive and significant’’effect on repurchase’’decisions. 5) Customer satisfaction’’has a positive and significant effect on repurchase’’decisions.